(untitled) (Journal of Science and Technology, 2016)
Nitrogen use efficiency is a measure of the extent to which a crop transforms available N to economic yield. Poultry manure is often reported to have lower N use efficiency than mineral fertilizer in the first year of application. However, under certain conditions such as rate of application, N mineralization rate, type of soil and crop, the converse may be the case. Will a farmer be better off in applying poultry manure at a particular rate than mineral fertilizer? A study was conducted on a forest acrisol to determine the physiological and apparent N efficiencies of poultry manure (PM) applied at various rates and mineral fertilizer to maize. Poultry manure rates of 2, 4, 6, 8 and 2 x 2 t ha-1 (i.e. split application) showed higher physiological N use efficiencies than the mineral fertilizer rate of 60-40-40 kg NPK ha-1 and 2 t PM ha-1 + 30-20-20 kg NPK ha-1. However, the mineral fertilizers (including combined half rate plus 2 t poultry manure) had the highest apparent N use efficiencies of 58% and 40% respectively, but low physiological N use efficiency. Among the poultry manure treatments, 4 t ha-1 with the highest N content of 2.17% in the maize ear leaves and grain N content of 12.56 g kg-1, had the highest physiological N use efficiency of 60 kg ha-1 making it the most efficient rate in the transformation of N into grain yield.